Pengembangan Wisata Argowisata Sukapulang di Desa Sukasetia Kecamatan Cihaurbeuti Kabupaten Ciamis - Ayu Yuliani; Asep Nurwanda; Hasna Nurfaidah; Rika Sri Wahyuni; Wisnu Eko Yuniaryuda (Jurnal Hukum dan Sosial Politik, 2025)
Sukasetia Village in Cihaurbeuti District has great potential to develop into a sustainable agrotourism destination. This study focuses on identifying strategic approaches to develop agrotourism in the Sukapulang area by employing a participatory method involving local communities as active stakeholders. The research adopts qualitative methods, including in-depth interviews, participatory observations, and descriptive analysis. Results indicate that agrotourism development can provide significant economic benefits, such as creating alternative income sources and preserving local culture and traditions. Furthermore, it enhances community engagement and promotes sustainable tourism practices aligned with global trends. Despite its potential, challenges remain, including inadequate infrastructure, limited access to information, and insufficient promotional strategies. The study recommends improving infrastructure, enhancing digital promotion, and implementing capacity-building programs to empower local communities. These strategies aim to ensure long-term sustainability and competitiveness for the agrotourism initiative. The findings suggest that with collaborative efforts involving local stakeholders, government, and private sectors, Sukasetia Village can serve as a model for community-based sustainable tourism development in rural areas, contributing positively to the region's economic and social growth.